2018
DOI: 10.1111/ijcs.12498
|View full text |Cite
|
Sign up to set email alerts
|

Factors shaping the financial capability of low‐income consumers from rural regions of Poland

Abstract: The two‐fold purpose of this study was to explore the financial capability of low‐income consumers from rural regions of Poland, using Xiao’s financial capability index, while accounting for their poverty status, demographic and financial characteristics. To test the relevant hypothesis of the study, a micro database of low‐income consumers was used. Factor, descriptive and correlation analyses were employed for preliminary examinations. One‐way ANOVA was used to examine the impact of different poverty indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 80 publications
2
38
0
8
Order By: Relevance
“…The core findings of this study established that financial behaviour has a significant impact on the financial capability of individuals. This agrees with other studies which indicated that financial behaviour is an essential factor to determine a person's financial capability (Potocki & Cierpiał-Wolan, 2019;Xiao, Chen, et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The core findings of this study established that financial behaviour has a significant impact on the financial capability of individuals. This agrees with other studies which indicated that financial behaviour is an essential factor to determine a person's financial capability (Potocki & Cierpiał-Wolan, 2019;Xiao, Chen, et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…Higher knowledge results in better financial behaviour which in return can enhance higher financial capability and control, with higher capability an individual can plan financial commitments, better financial planning and cash flows in much better ways. As mentioned earlier, financial behaviour is a core element that shapes the level of financial capability (Potocki & Cierpiał-Wolan, 2019), and financial knowledge precedes financial behaviour (Hayhoe et al, 2005;Potrich et al, 2016;Yong et al, 2018). Learning financial topics can improve attitudes and behaviours, and in the long run, it can enhance financial capability (Batty et al, 2015).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations